Successful Application of Argatroban During VV-ECMO in a Pregnant Patient Complicated With ARDS due to Severe Tuberculosis: A Case Report and Literature Review - Wu, Hongxia; Tang, Yongjiang; Xiong, Xiaofeng; Zhu, Min; Yu, He; Cheng, Deyun (Frontiers in Pharmacology, 2022)
Background: Severe tuberculosis in pregnancy may progress to acute respiratory distress syndrome (ARDS). Veno-venous extracorporeal membrane oxygenation (VV-ECMO) should be considered if conventional lung-protective mechanical ventilation is failed. Heparin-induced thrombocytopenia (HIT) is often occurred during ECMO. Alternative anticoagulant therapy during ECMO in pregnant patients with thrombocytopenia is unclear. Case summary: We described for the first time a case report of ARDS induced by severe tuberculosis successfully recovered from VV-ECMO with anticoagulant of argatroban in a pregnant patient. In addition, we revised existing literature on VV-ECMO and/or argatroban in pregnant patients. A 31-year-old woman at 17 weeks of gestation was transferred to our hospital for ARDS secondary to severe tuberculosis. VV-ECMO was initiated after protective ventilation strategies and other conventional therapies. UFH was chosen as the initial anticoagulant therapy. On day 3, the patient's platelet count and anti-thrombin III declined to 27 × 103 cells/μL and 26.9 %, respectively. The patient was commenced on infusion with argatroban at a rate of 0.06 μg/kg/min. The maintained dose infusion of argatroban varied from 0.9-1.2 ug/kg/min. The actual APTT and ACT ranged from 43 seconds to 58 seconds and 220 seconds to 260 seconds without bleeding or thrombosis. The patient weaned from VV-ECMO on day 27 and discharged hospital finally. Conclusion: VV-ECMO may be considered in ARDS refractory to conventional treatments in pregnancy. Argatroban may be an alternative option in pregnant patients during ECMO with thrombocytopenia and anti-thrombin III deficiency.